(untitled) (INNOVATIVE ECONOMY, 2026)
Kostetskyi Ya.I. CURRENT TRENDS IN THE DEVELOPMENT OF ENERGY MANAGEMENT AT UKRAINIAN ENTERPRISES Purpose. The aim of the study is to investigate current trends in the development of energy management at domestic enterprises, identify the main challenges to its functioning under energy and economic pressures, and substantiate promising directions for enhancing the energy efficiency and energy resilience of enterprises. Methodology of research. A complex of general scientific and specialized methods was applied in the research process, including: methods of theoretical generalization and systematization – to define the essence of energy management; comparative analysis – to study global and domestic trends in energy management development; statistical method – to evaluate the dynamics of energy efficiency and the implementation of energy management systems; and systemic and structural approaches – to substantiate directions for improving energy management at enterprises. Findings. The article examines the current state of energy management development at Ukrainian enterprises and identifies the key drivers of its transformation amidst military operations, energy instability, and Euro-integration processes. The impact of digitalization, renewable energy, energy monitoring systems, and the ISO 50001 standard on improving the efficiency of energy consumption management is analysed. The study substantiates the expediency of transitioning from the traditional energy-saving model to the concept of energy resilience and enterprise autonomization. Directions for the development of digital energy management and decentralized energy generation are proposed. Originality. The scientific novelty of the research lies in substantiating current trends in the transformation of energy management in Ukraine under military and energy challenges. The approaches to interpreting energy management have been enhanced, defining it as a system that ensures not only energy efficiency but also the energy resilience of enterprises. Provisions regarding the integration of digital technologies, energy monitoring systems, and decentralized generation sources into the corporate energy management architecture have been further developed. Practical value. The practical significance of the findings lies in the feasibility of utilizing the proposed recommendations to improve energy management systems at Ukrainian enterprises. The results of the study can be applied in formulating energy efficiency strategies, implementing digital energy consumption management systems, developing measures to enhance energy resilience, and adapting enterprises to modern economic and energy challenges. Key words: energy management, energy efficiency, energy resilience, digitalization, ISO 50001, renewable energy, decentralized generation, energy monitoring, energy security.